NON-STATE ACTORS IN WORLD POLITICS:: A CHALLENGE TO NATION-STATES? - Orogbemi, Elias Olajide (Journal of Contemporary International Relations and Diplomacy, 2021)
In international politics, the discussion has always essentially focused on the sovereignty of nation-states. Nation-states are widely viewed as the only important actors in world politics. However, nation-states are by no means the only politically and economically significant actors in world politics. In the post-World War II era, non-state actors were recognized as having an important impact on world politics. This paper critically examines the ways in which and the extent to which the emergence of non-state actors such as Multinational Corporations, Transnational Advocacy Networks, Transnational Diaspora Communities, and Violent Non-State Actors in world politics affects the relevance of nation-states who were initially regarded as the sole actor in world politics from the realist perspective. The complex interdependence theory is adopted as the framework of analysis. This study uses qualitative research method of analysis, and lean only on secondary data. The findings show that the state-centric image of world politics is both inaccurate and potentially damaging for the analysis of world politics. A state-centric focus, no matter its level of sophistication, can limit the ability of both academics and policymakers to describe, explain, and manage the complexity of the world arena. Non-state actors are making their contributions, both positively and negatively, to the state system.